Research on Technology to Protect and Utilize Insect Natural Enemies in Sustainable Agriculture - Chen Jieyu (SHS Web of Conferences)
With the increasing global attention to environmental protection and food safety, sustainable agriculture has been widely adopted as a way to reduce the impact on the environment and maintain the ecological balance of agriculture. As an important part of sustainable agriculture, research into the protection and utilization of natural enemy insects aims to control pest populations naturally by maintaining and increasing beneficial insect populations, thereby reducing the use of chemical pesticides. This study overviews the strategy to protect and use natural enemies of insects for sustainable agriculture. It analyzes the challenges we encounter in the practical application and its future development pathways. First, this paper introduces the classification and importance of insect natural enemies. It summarizes general conservation and application methods such as habitat management, biological pesticides, and artificial propagation and release techniques. Second, this paper discusses ecological factors such as biodiversity, food web structure, and farmland microenvironment that must be considered when adopting these strategies. Additionally, it evaluates the effects of controlling pests after using these techniques and finds ways to optimize them, thereby improving their efficiency and stability. This study highlights implementation issues, such as natural enemy selectivity, adaptability, and persistence, and how to tailor conservation and use programs in diverse agricultural ecosystems. Finally, this study emphasizes the necessity of expanding research fields, strengthening interdisciplinary cooperation, and promoting the application of knowledge. It also emphasizes the contribution of rational planning and scientific management of natural enemy resources to future agricultural sustainability.